Transcript variants of long-chain acyl-CoA synthase 1 have distinct roles in sheep lipid metabolism - Cao, Yang; Yu, Yongsheng; Zhang, Lichun; Liu, Yu; Zheng, Kaizhi; Wang, Sutian; Jin, Haiguo; Liu, Lixiang; Cao, Yang (Frontiers in Genetics, 2022)
Mutton has recently been identified to be a consumer favorite, and intermuscular fat is the key factor in determining meat tenderness. Long-chain acyl-CoA synthetase 1 (ACSL1) is a vital subtype of the ACSL family that is involved in the synthesis of lipids from acyl-CoA and the oxidation of fatty acids. The amplification of the ACSL1 gene using rapid amplification of cDNA ends revealed that the alternative polyadenylation (APA) results in two transcripts of the ACSL1 gene. Exon 18 had premature termination, resulting in a shorter CDS region. In this study, the existence of two transcripts of varying lengths translated normally and designated ACSL1-a and ACSL1-b was confirmed. Overexpression of ACSL1-a can promote the synthesis of an intracellular diglyceride, while ACSL1-b can promote triglyceride synthesis. The transfection of ACSL1 shRNA knocks down both the transcripts, the triglyceride content was significantly reduced after differentiation and induction; and lipidome sequencing results exhibited a significant decrease in 14–22 carbon triglyceride metabolites. The results of the present study indicated that the ACSL1 gene played a crucial role in the synthesis of triglycerides. Furthermore, the two transcripts involved in various interactions in the triglyceride synthesis process may be the topic of interest for future research and provide a more theoretical basis for sheep breeding.